Circulating concentrations of folate and vitamin B12 in relation to prostate cancer risk: results from the European Prospective Investigation into Cancer and Nutrition study. - Johansson, M; Appleby, P; Allen, N; Travis, R; Roddam, A; Egevad, L; Jenab, M; Rinaldi, S; Kiemeney, L; Bueno-de-Mesquita, H; Vollset, SE; Ueland, P; et al. (2008)
BACKGROUND: Determinants of one-carbon metabolism, such as folate and vitamin B(12), have been implicated in cancer development. Previous studies have not provided conclusive evidence for the importance of circulating concentrations of folate and vitamin B(12) in prostate cancer etiology. The aim of the present study was to investigate the relationship between prostate cancer risk and circulating concentrations of folate and vitamin B(12) in a large prospective cohort. METHODS: We analyzed circulating concentrations of folate and vitamin B(12) in 869 cases and 1,174 controls, individually matched on center, age, and date of recruitment, nested within the European Prospective Investigation into Cancer and Nutrition cohort. Relative risks (RR) for prostate cancer were estimated using conditional logistic regression models. RESULTS: Overall, no significant associations were observed for circulating concentrations of folate (P(trend) = 0.62) or vitamin B(12) (P(trend) = 0.21) with prostate cancer risk. RRs for a doubling in folate and vitamin B(12) concentrations were 1.03 [95% confidence interval (95% CI), 0.92-1.16] and 1.12 (95% CI, 0.94-1.35), respectively. In the subgroup of cases diagnosed with advanced stage prostate cancer, elevated concentrations of vitamin B(12) were associated with increased risk (RR for a doubling in concentration, 1.69; 95% CI, 1.05-2.72, P(trend) = 0.03). No other subgroup analyses resulted in a statistically significant association. CONCLUSION: This study does not provide strong support for an association between prostate cancer risk and circulating concentrations of folate or vitamin B(12). Elevated concentrations of vitamin B(12) may be associated with an increased risk for advanced stage prostate cancer, but this association requires examination in other large prospective studies.